An ecology of trust? Consenting to a pluralist universe. Issue 2 (March 2022) - Debaise, Didier; Stengers, Isabelle
The idea of 'progress' was undoubtedly at the heart of the experience of the Moderns, guiding at the same time their thought, the values that they gave themselves, the hopes that animated them and of innumerable justifications that they found for all the processes of dispossession, disqualification and dismemberment that they implemented. Starting with William James's diagnosis of the hold the idea of 'progress' has over us, and following his proposition that this idea is at work in the world itself, in the ecological and social ravages that it guides and justifies, this article aims to analyse the political and speculative effects of the notion of progress and to propose, through what we call an 'ecology of trust', other ways of collectively composing our modes of existence.